2016
DOI: 10.1177/0194599816663924
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Angiotensin‐Modulating Antihypertensives on Time Interval to Revision Surgery for Nasal Polyps

Abstract: Use of ACEIs and ARBs is associated with an increased time to revision sinus surgery among patients with concurrent nasal polyps and asthma. A possible mechanism of this observed effect is suppression of periostin expression through inhibition of the angiotensin pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, given primarily for their antihypertensive and cardioprotective effects, have been shown to reduce expression of periostin and have been linked to delayed polyp regrowth. 17,19,28 We hypothesize that these observed effects reflect inhibition of periostin production by these agents, which may lead to the slowing of polyp formation. Other potential biomarkers and therapeutic targets have been described for CRS, including p-glycoprotein targeted by verapamil, 29 cysteinyl leukotriene targeted by leukotriene receptor antagonists, 30 circulating IgE targeted by omalizumab, 31 and IL-5 targeted by mepolizumab.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, given primarily for their antihypertensive and cardioprotective effects, have been shown to reduce expression of periostin and have been linked to delayed polyp regrowth. 17,19,28 We hypothesize that these observed effects reflect inhibition of periostin production by these agents, which may lead to the slowing of polyp formation. Other potential biomarkers and therapeutic targets have been described for CRS, including p-glycoprotein targeted by verapamil, 29 cysteinyl leukotriene targeted by leukotriene receptor antagonists, 30 circulating IgE targeted by omalizumab, 31 and IL-5 targeted by mepolizumab.…”
Section: Discussionmentioning
confidence: 96%
“…18 In a recent study by Brook et al, we found that the use of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in patients with nasal polyps and asthma significantly delayed the time to revision sinus surgery by >2 years, suggesting a possible mechanism by which polyp formation can be influenced through inhibition of periostin expression. 19 Given these findings, we sought to explore the role of periostin expression in the development of nasal polyps. The purpose of the current study was to measure serum periostin levels in patients with sinonasal disease and controls to determine the applicability of periostin as a potential molecular biomarker for CRS and its endotypes.…”
mentioning
confidence: 99%
“…Additional potential MMP modulators may include simvastatin (in vitro studies) (72) , angiotensin converting enzyme inhibitors and angiotensin receptor blockers (case series) (73) .…”
Section: Pharmaceutical Agentsmentioning
confidence: 99%
“…Diagnostic tests for human immunodeficiency virus (HIV), tuberculosis, syphilis and hepatitis should be considered in patients with high-risk exposure to infectious diseases. Th2-type asthma (66)(67)(68) . Serum periostin levels also appear to be higher in patients with NSAID intolerance than in those without it (67) .…”
Section: Infectious Conditionsmentioning
confidence: 99%